Hemoperitoneum from splenic rupture in an expatriate - Tonolini, Massimo (Medknow Publications & Media Pvt Ltd, 2012)
Splenic rupture with hemoperitoneum represents a life-threatening surgical emergency. Malaria should be highly suspected as the probable underlying disease in returning travellers, expatriates, or recent immigrants from endemic countries. Malarial complications involving the spleen occur even with appropriate prophylaxis or during antimalarial therapy. Among them, splenic infarction has a favourable course and is treated conservatively, whereas life-threatening rupture requires immediate or delayed splenectomy. Computed tomography (CT) allows confident differentiation between these two complications by identifying ruptured spleen with clotted hematoma and associated high-density peritoneal effusion; furthermore, CT allows differential diagnosis from other causes of spontaneous hemoperitoneum.